SOURCES OF MATERIAL CULTURE OF CHAGANIYAN - TURSUNOV ANVAR SAYPULLAEVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article, the city of Chaghaniyan is larger than Termez in terms of area, but Termez is superior to Chaghaniyan in terms of its population and wealth. In short, “the city of Chaghaniyon has been glorified in all sources as one of the most culturally advanced, scientifically advanced central cities of northern Tokharistan for the last three hundred years.